Challenging Constant Ambiguity: Modern Legal Approaches to Asylum (Polish Yearbook of International Law, 2021)
Legal understandings of asylum vary and remain to a great extent ambiguous. This is because asylum takes different legal forms in different legal dimensions: general international law, international human rights law, EU law, and constitutional law. All the above-mentioned dimensions are strictly linked and combined. Yet the ways in which asylum has been addressed, especially in the doctrine, often overlook this complexity. This article is aimed at assessing the modern legal approaches to the institution of asylum in international, European, and domestic legal orders, with reference to the positions taken by the late Janusz Symonides and in this way commemorating his recent passing away.